On the global warping of a thin self-gravitating near Keplerian gaseous disk with application to the disk in NGC 4258 - Papaloizou, J; Terquem, C; Lin, D (1997)
On the global warping of a thin self-gravitating near Keplerian gaseous disk with application to the disk in NGC 4258